The water striders (Hemiptera: Heteroptera: Gerridae) of Costa Rica: new species, checklist, and new records - Pacheco-Chaves, Bernald; Cordeiro, Isabelle Da Rocha Silva; Moreira, Felipe Ferraz Figueiredo; Springer, Monika (Zootaxa, 2018)
Brachymetra bernaldi Cordeiro, sp. nov. (Hemiptera: Heteroptera: Gerridae) from Heredia, Costa Rica, is herein described, illustrated, and compared with congeners. The new species resembles B. albinervus (Amyot & Serville, 1843), but can be separated from it by the weak median carina of the pronotum, male abdominal mediotergite I with weak lateral notches, male abdominal mediotergite VII quadrate, male abdominal segment VIII in natural position almost entirely inserted into the abdominal cavity, and paramere narrow, with acute apex. We also provide the first checklist of the Gerridae of Costa Rica and new records, based on collection material and field sampling. All totaled, 31 species representing 13 genera and six subfamilies are recorded from the country. Five species and the genera Brachymetra Mayr, 1865 and Neogerris Matsumura, 1913 are registered for the first time from Costa Rica, and new provincial records are presented for 15 other species.